Peranan permainan tradisional dalam mengembangkan kemampuan matematika anak usia sekolah dasar - Nurdiana Siregar; Wiwiek Lestari (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2018)
Math is never separated from the activities of life, not least the traditional game. The study aims to 1) describe the types of traditional games related to mathematical activities, 2) examine the role of traditional children's games in the practice of numeracy skills, and 3) examine the role of traditional children's games in introducing flat shape to children in Hamparan Perak Village. This study used a qualitative approach that the data obtained were analyzed descriptively. The subjects of this study are elementary school children (SD) who are domiciled in Hamparan Perak Village. Data collection techniques are observation, interview, and documentation. The results of the research are: 1) traditional game types that have the mathematical activities of traditional games, complexes, marbles and rocks, 2) traditional games to train children to count, recognize numbers, and numeracy skills such as addition and multiplication, 3) traditional games making children will be lines, rectangles, rectangles, and triangles.